Add the polynomials: (xy + 3x + 2) + (3x2 + y)

Mathematics
Tutor: None Selected Time limit: 1 Day

just doing homework

Nov 25th, 2014

(xy + 3x + 2) + (3x^2 + y)

Opening the brackets, we get

= xy + 3x + 2 + 3x^2 + y

Now 

= 3x^2 + 3x + 2 + xy + y 

= 3x^2 + 3x + 2 + y(x + 1) 

= 3x(x + 1) + y(x + 1) + 2

= (x + 1)[3x + y + 2]

Hence     (xy + 3x + 2) + (3x^2 + y) = (x + 1)[3x + y + 2]

Nov 25th, 2014

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Nov 25th, 2014
...
Nov 25th, 2014
May 29th, 2017
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer